Hubungan Jenis Kelamin dan Usia dengan Kejadian Faringitis Akut di Puskesmas Tanjung Rejo Tahun 2025 - Jerry Tobing (Majalah Ilmiah METHODA, 2026)
Acute respiratory tract infection (ARI) is one of the health problems frequently found in primary health care facilities. Pharyngitis is included in the group of ARI that frequently occurs, both in children and adults. Age and gender factors are thought to play a role in the variation of pharyngitis incidence compared to non-pharyngitis ARI. To determine the relationship between age and gender and the incidence of pharyngitis compared to non-pharyngitis ARI at Tanjung Rejo Health Center in 2025. This study used an analytical design with a cross-sectional approach. The study population was all patients with a diagnosis of ARI based on medical records at Tanjung Rejo Health Center in 2025, totaling 483 patients. Samples were taken using al simple random sampling technique with the Slovin formula, resulting in a sample size of 219 respondents. Data were analyzed using the chi-square statistical test (p<0.05). The results of the study showed that there was a relationship between age and the incidence of pharyngitis and non-pharyngitis ARI (p value = 0.004), and there was no significant relationship between gender and the incidence of pharyngitis and non-pharyngitis ARI (p value = 0.359). There was a significant relationship between age and the incidence of pharyngitis compared to non-pharyngitis ARI, but there was no significant relationship between gender and the incidence of pharyngitis compared to non-pharyngitis ARI at Tanjung Rejo Health Center in 2025.